Evaluasi Efektivitas Antibiotik Komersil Terhadap Agen Penyebab Gejala Snot pada Ayam Broiler di Kabupaten Kupang - Soge, Bergitha; Tangkonda, Elisabet; Widi, Antin Y. N.; Sanam, Maxs U. E.; Deta, Herlina Umbu (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2023)
Snot is a symptom of upper respiratory system infections in poultry, characterized by exudate production from the nasal cavity, swelling of infraorbital sinuses, snoring, sneezing, and dyspnoea. The aetiology of snot that have been isolated are Avibaterium paragallinarum, Pasteurella multocida, Ornithobacterium rhinotracheale, and Mycoplasma sp. Snot symptom can be eradicated with antibiotic treatment; however, antibiotic resistance makes antibiotic treatment ineffective. This study is aimed to evaluate the effectiveness of some commercial antibiotics against bacteria isolated from broiler chicken with snot symptom in Kupang Regency. Amoxycillin, ampicillin, tetracycline, cefoxitin, and ciprofloxacin were tested using the Kirby Bauer method with McFarland Turbidity Standard against Avibacterium paragallinarum, Ornithobacterium rhinotracheale, Pasteurella multocida, and Mycoplasma sp isolates. Inhibition zones were measured and compared to the standard of the Clinical Laboratory Standard Institute (CLSI) to determine the sensitivity or resistance percentage. The result showed that Avibacterium paragallinarum, Ornithobacterium rhinotracheale, Pasteurella multocida, and Mycoplasma sp were highly resistant to amoxycillin and ampicillin, yet most sensitif to ciprofloxacin. This suggests commercial antibiotics that are productive to eradicate snot symptom and implies some antibiotics that are ineffective to overcome snot symptom and hence should not be used in the field.